An Extension of the Mittag-Leffler Function and Its Associated Properties - Gauhar Rahman; Abdus Saboor; Zunaira Anjum; Kottakkaran Sooppy Nisar; Thabet Abdeljawad (Advances in Mathematical Physics)
Inspired by certain fascinating ongoing extensions of the special functions such as an extension of the Pochhammer symbol and generalized hypergeometric function, we present a new extension of the generalized Mittag-Leffler (ML) function εa,b;p,vκz1 in terms of the generalized Pochhammer symbol. We then deliberately find certain various properties and integral transformations of the said function εa,b;p,vκz1. Some particular cases and outcomes of the main results are also established.